Efek Insektisida Aromaterapi Minyak Atsiri Daun Nilam (Pogostemon cablin Beth) Terhadap Aedes aegypti: The Insecticide Effect of Patchouli leaves (Pogostemon cablin Beth) Essential Oil Aromatherapy Candle Against Aedes aegypti - Raihan, Azmi; Novyan Lusiyana (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Aromatherapy candles are a safe and effective insecticide innovation with a long-lasting fragrance. Aromatherapy candles can also act as an adulticide for mosquitoes if made from the essential oil of patchouli leaves that have natural insecticidal properties against Aedes aegypti mosquitoes. This research aims to determine the adulticidal effect of patchouli leaves (Pogostemon cablin Benth) essential oil aromatherapy candle against Ae. aegypti mosquitoes. This research is experimental with a post-test only control group design divided into six groups: one negative control group and five treatment groups (25, 40, 55, 70, and 85%) with four repetitions. Each group consisted of 20 Ae. aegypti mosquitoes. Before testing, the aromatherapy candle was lit in the test room for three hours and then extinguished. The mosquitoes were exposed to the vapor produced by patchouli essential oil aromatherapy candles for five hours, and the mortality rate was assessed every hour. Afterward, the data were analyzed using One-way ANOVA, post hoc Bonferroni and probit analyses. The average mosquito mortality rate was 0% in the negative control group and 25; 32.5; 51.25; 70; and 87.5% in the treatment groups of 25, 40, 55, 70, and 85%, respectively. The data analysis indicated a significant difference in the mosquito mortality rate in all treatment groups (p<0.05) with a 95% confidence interval. Meanwhile, the probit analysis showed an LC50 of 63% and LC90 of 96.067%. We conclude that the aromatherapy candle made from patchouli essential oil had an adulticidal effect on Ae. aegypti mosquitoes.